“Estranxeira na súa patria” by Rosalía de Castro: Identity Denied in one’s Own Homeland - García Negro, María Pilar (Madrygal. Revista de Estudios Gallegos, 2015)
Rosalía de Castro is the author of immortal verses, phrases and sentences which are destined to endure, not only because of their uniqueness but also because they are evidence of a philosophical, psychological and political content of great accuracy and depth. A singular example is the title of her poem “Estranxeira na súa patria”. We will study its contents and significance in the light of all the works ever written by the author.